Design of Gas-Cooled Fast Reactor 600MWth with Natural Uranium As Fuel Circle Input - Menik Ariani; Zaki Su’ud; Fiber Monado (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2013)
This article presents the conceptual design of gas-cooled fast reactor (helium), the small size of the long-lived 600 MWth. Early stages of the design is to determine the geometry of the terrace, the value of the volume fraction and the mass fraction of fuel, cladding and coolant structure to calculate the parameters of reactivity, burnup, power distribution and density changes nuclides U238 and Pu239. The calculation is done using SRAC-CITATION code. SRAC code with JENDL-3.2 Data nuclides produced macroscopic cross section values for the eight energy group. Multi-group numerical solution of diffusion equations for 2-D geometry terrace RZ performed by CITATION code. The study results showed that the scheme Modified CANDLE, thermal power output is 600 MWth, with a fuel cycle for 10 years. This reactor has the advantage of requiring only the input of natural uranium in the fuel cycle, without the need for enrichment processes that affect the economic value. Keywords : Reactor, natural uranium, modified candle, burnup